2020
DOI: 10.1038/s41598-020-62104-w
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot all-optical switching of magnetization in Tb/Co multilayer-based electrodes

Abstract: Ever since the first observation of all-optical switching of magnetization in the ferrimagnetic alloy GdFeCo using femtosecond laser pulses, there has been significant interest in exploiting this process for data-recording applications. in particular, the ultrafast speed of the magnetic reversal can enable the writing speeds associated with magnetic memory devices to be potentially pushed towards tHz frequencies. this work reports the development of perpendicular magnetic tunnel junctions incorporating a stack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 30 publications
3
62
0
Order By: Relevance
“…All optical switching (AOS) of magnetization using ultrashort laser pulses, whether it is helicity dependent [1][2][3][4][5][6] or helicity independent (AO-HIS), [4,[6][7][8][9][10][11][12] exhibits a very interesting out of equilibrium physics as well as promising practical implications. [13] Many attempts to unveil the detailed mechanism of those phenomena have been carried out both theoretically [8,[14][15][16][17][18][19][20][21][22][23][24] and DOI: 10.1002/advs.202001996 experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All optical switching (AOS) of magnetization using ultrashort laser pulses, whether it is helicity dependent [1][2][3][4][5][6] or helicity independent (AO-HIS), [4,[6][7][8][9][10][11][12] exhibits a very interesting out of equilibrium physics as well as promising practical implications. [13] Many attempts to unveil the detailed mechanism of those phenomena have been carried out both theoretically [8,[14][15][16][17][18][19][20][21][22][23][24] and DOI: 10.1002/advs.202001996 experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Many attempts to unveil the detailed mechanism of those phenomena have been carried out both theoretically [8,[14][15][16][17][18][19][20][21][22][23][24] and DOI: 10.1002/advs.202001996 experimentally. [1][2][3][4][5][6][7][8][9][10][11][12][25][26][27][28] AO-HIS is observed after a single femtosecond laser pulse and most of the materials showing this effect are gadolinium-based rare earth (RE)/transition metals (TMs) ferrimagnets. [24] AO-HIS has been extensively studied in amorphous GdFeCo alloy.…”
Section: Introductionmentioning
confidence: 99%
“…All-optical switching (AOS) of magnetization using a single ultrashort laser pulse in the absence of a magnetic field [5] was first identified in amorphous ferrimagnetic Gd x (FeCo) 100−x thin films (hereafter referred to as GdFeCo) in 2012 [6]. Great efforts have since been devoted by experimentalists and theoreticians alike to unravel the underlying physical mechanism, with the ultimate aim of designing alternative optically switchable materials with superior functionality [7,8].…”
mentioning
confidence: 99%
“…Although, we have used the same damping constant value for Tb and Co atoms to determine the switching probability, as was done in similar works 14 , 25 , the exploration of element-specific damping could provide more information about the switching dynamics of the system as suggested by recent reports 28 . Our simulation and experiments 12 were performed using fs-long pulses to evaluate the optical switching in [Tb/Co]-based systems and only [ / ] and [ / ] showed a clear fluence window for the observation of optical switching using 50 fs pulses (Fig. S2 in the Supplementary data file).…”
Section: Dynamic Magnetic Properties Of [ ] Multilayersmentioning
confidence: 99%
“…For instance, systematic experimental studies on the switching ability of RE-based and RE-free multilayered systems performed by El-Hadri et al 8 , demonstrated that engineered synthetic ferrimagnets such as [Ho/Co], [Tb/Co] and [Co/Pt] based multilayers only show HD-AOS. Among all systems switched by HD-AOS, only a few multilayered systems exhibit the possibility of single-shot switching: Pt/Co/Pt/Co/GdFeCo 9 , Pt/Co/Gd 10 , FeCoB/Ta/[Tb/Co] 11 , 12 and Pt/Co/Pt 13 . From a theoretical point of view, only two reports discuss the possibility of TIMS in alloys 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%